Les sculptures coptes de Tôd au musée du Louvre - Meurice, Cédric (Journal of Coptic studies, 2025)
At the end of the first excavations campaigns in Tôd, between 1933 and 1950, under the responsibility of the Louvre Museum and the archaeologist Fernand Bisson de La Roque, several archaeological items were shared between the Louvre Museum (the concession holder) and the 'Service des Antiquités' of Egypt. This article focuses on a corpus of nineteen Coptic lapidary pieces from these excavations, which were discovered between 1933 and 1936 and entered the collections of the Louvre Museum, in the Department of Egyptian Antiquities. The creation of the Department of Byzantine and Eastern Christian Art has prompted us to retrace the movements and life of these objects from their discovery to their entry into the national collections, and to re-examine their decoration.